Single stock futures : - Mitchell, Kennedy (Wiley, 2003)
In Single Stock Futures: An Investor’s Guide, author Kennedy Mitchell introduces you to single stock futures, explains how they function, and demonstrates the various ways they can be traded. This comprehensive guide clearly illustrates how investors–both individual and professional–can utilize single stock futures independently or as an application to add new dimensions to an investment portfolio